A produção do conhecimento na Revista Brasileira de Ciências do Esporte sobre equidade de gênero nas aulas de educação física da escola - Vanessa Bonfim Castro (2023)
The Revista Brasileira de Ciências do Esporte (RBCE) is considered one of the main scientific publications in the area of Physical Education and sports in Brazil, and, therefore, this periodical was used as a relevant way to understand the gender issues present in school physical education classes. Thus, this study had as its object of investigation the academic productions published in RBCE, in the period between 1979 and 2023, with the challenge of reflecting on the trajectory of this theme in the magazine, as well as understanding the perceptions and contributions of different authors. in the production of this knowledge. To identify and analyze the trends and theoretical-methodological gaps regarding gender issues in the magazine, the State of the Art was carried out, a bibliographical research, carried out through the survey, mapping and analysis of data from the entire scientific production of the magazine. RBCE, which covered the theme of gender and Physical Education at school throughout the periodical's more than 40 years of existence. This survey resulted in 15 articles identified for study, to which we had access in full, all available in the online version. Based on the findings of RBCE and the observations and considerations of the authors who spoke about this theme that is so emblematic in the magazine, as an educational product, a didactic unit was created, the aim of which was to raise propositions capable of tackling the gender issues present in schools, assisting teachers to address these discussions that emerge from pedagogical praxis and contribute to minimizing machismo and prejudice against women, still so present in our daily lives, aiming to offer effective pedagogical support to encourage inclusive and egalitarian practices at school.